2011
DOI: 10.1007/s11258-011-9902-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use intensity and temperature on the reproductive performance of Dactylis glomerata populations in the southeastern Alps

Abstract: An understanding of the processes and environmental conditions governing spatial variation in reproductive performance of plants can provide important information about the factors characterizing plant community structure and influencing fitness in natural plant populations, especially in the context of climate and land use change. In this study, 60 mountain populations of Dactylis glomerata distributed along a fertilization regime in varying grassland hay meadows were evaluated. Variations in field management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Differences in intraspecific flowering time and overall reproduction output (i.e., seed mass production) across tree/shrub/herbaceous populations along latitudinal and altitudinal gradients has also been documented, suggesting longer flowering intervals and greater reproduction output in southern than northern populations (Sills and Nienhuis 1995;Tungate et al 2002;Bohlenius et al 2006;Hall et al 2007;Breen and Richards 2008;Chuine 2010;Dainese 2011). For instance, Dainese (2011) found variation in the reproductive performance of Dactylis glomerata across hay meadows in an elevational gradient with low-elevation individuals having larger inflorescences and larger seed masses than higher elevation individuals, meaning higher reproductive output in warmer/longer growing seasons than in colder/shorter growing seasons. Dainese (2011) suggested that longer growing seasons and/or warmer climates in lower elevation sites promote higher photosynthetic rates (i.e., greater C acquisition toward growth) and/or higher nutrient availability generating greater plant allocation toward reproductive performance than colder climates in higher elevations.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in intraspecific flowering time and overall reproduction output (i.e., seed mass production) across tree/shrub/herbaceous populations along latitudinal and altitudinal gradients has also been documented, suggesting longer flowering intervals and greater reproduction output in southern than northern populations (Sills and Nienhuis 1995;Tungate et al 2002;Bohlenius et al 2006;Hall et al 2007;Breen and Richards 2008;Chuine 2010;Dainese 2011). For instance, Dainese (2011) found variation in the reproductive performance of Dactylis glomerata across hay meadows in an elevational gradient with low-elevation individuals having larger inflorescences and larger seed masses than higher elevation individuals, meaning higher reproductive output in warmer/longer growing seasons than in colder/shorter growing seasons. Dainese (2011) suggested that longer growing seasons and/or warmer climates in lower elevation sites promote higher photosynthetic rates (i.e., greater C acquisition toward growth) and/or higher nutrient availability generating greater plant allocation toward reproductive performance than colder climates in higher elevations.…”
Section: Discussionmentioning
confidence: 99%
“…The mean seed mass was calculated by dividing the mass of harvested seeds by the number of counted seeds, since using threshold of seed mass per 100 seeds was not feasible due to that some genotypes plants produced far less number of seeds (Kéry et al, 2000). Lastly, the total number of seeds per individual plant was calculated as the total seed mass per plant divided by the mean seed mass (Snow et al, 2003;Dainese, 2011).…”
Section: Fecundity Calculationmentioning
confidence: 99%
“…Plants are variable and heritable variability causes some individual plants to reproduce and establish better than others (Pringle, Chen, & Taylor, 2003). Understanding the processes and environmental conditions governing plant variation in reproductive performance is essential and provides important information on factors that characterise plant community structure and influence fecundity (Dainese, 2011). Plant variation arises due to the different parameters used when comparing fecundity associated with different characters, such as states of flowering or fruiting, related plant attributes such as fruit set and seed mass, germination rates and seed number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sexual reproductive phase in plants might be particularly vulnerable to the effects of global warming. The direct effect of temperature changes on the reproductive process has been previously documented, and recent data from other physiological processes that are affected by rising temperatures reinforce the concept that reproductive process are susceptible to a changing climate [14,15,16,17]. Unraveling the effect of temperature on possible future vegetation range shifts compared with other local abiotic and biotic environmental variables is important [17].…”
Section: Introductionmentioning
confidence: 99%